Antimicrobial Potential of Polyherbal Formulation against Common Pathogens of Cow Mastitis - Sakthikarthikeyan, Sengamani; Manikandan, Rajendran; Madhupriya, Senthilkumar; Harigopal, Sreedharan (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Mastitis is a global problem, which affects the health of animal, milk quality and economics of milk production. Multidrug-resistant Staphylococcus aureus, Klebsiella pneumoniae, and Escherichia coli are found to be increased in mastitis cases. There is a growing need for finding alternatives to antibiotics in the prevention and treatment of mastitis infections. Polyherbal formulations (PHF) are safe with wide therapeutic range and effective at low dose compared to single herbal formulation. Equal concentration of ethanolic extract of Aerva lanata, Phyllanthus emblica, Cyperus rotundus and Boerhavia diffusa formulation was used to assess the in vitro antibacterial activity against mastitis milk isolates Staphylococcus aureus, Klebsiella pneumoniae and Escherichia coli by well diffusion, agar diffusion and MIC by resazurin dye method. Zone of inhibition was greater in polyherbal formulation than herbal standard quercetin due to synergistic effects of multiple numbers of bioactive constituents. Polyherbal formulation had one fold low MIC value than gentamicin and one fold high MIC value than quercetin against E. coli, S. aureus, K. pneumoniae. Antimicrobial activity of the polyherbal formulation could be due to quercetin, a plant flavonoid quantified by using High Performance Thin Layer Chromatography (HPTLC).
Keywords: Antimicrobial; Cow; Mastitis; MIC; Polyherbal; Quercetin